Nikah Sirri Versus Nikah Understand Acte: Perspective of Contemporary Islamic Law - Nawirman; Achmad Musyahid; Hartiningsih; Nurchamidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The perspective of contemporary Islamic law is a perspective that tries to see further how understand acte versus sirri marriage exists in the midst of modern human life as a phenomenon. An approach based on the responsive fiqh paradigm is a necessity in the development of contemporary Islamic law, including addressing sirri marriage versus understand acte marriage. In this process, a marriage that is carried out must be carried out through an understand acte marriage because with the registration of marriages at an official state institution, this will guarantee state protection with its normative juridical authority for the parties involve. Phenomenon of modern human life today which shows that marriage with sirri marriage raises various problems implies the need for contemporary Islamic law to emphasize that registration of marriage in an official state institution or understand act marriage is an aspect that needs to be considered to become a legal requirement of a marriage.